The dictionary of multimedia : terms & acronyms - Hansen, Brad. (Wilsonville, Or. : Franklin, Beedle & Associates, 2005)
Defines critical terms and concepts associated with computing and digital media, along with information on electronic copyright, programming languages, and operating systems.
Keywords: Computers -- Dictionaries; Digital media -- Dictionaries